Accuracy of Product Ingredient Labeling: Comparing Drugstore Products With Online Databases and Online Retailers. Issue 2 (March 2020) - Comstock, Jeanette R.; Reeder, Margo J.
Abstract : Background: Patients with allergic contact dermatitis rely on ingredient lists published in databases and by online retailers to find safe skincare products. Objective: The aim of this study was to determine the accuracy of product ingredient labeling by comparing drugstore product labels to ingredient lists published online. Methods: Amazon was queried for best-selling items in several categories of skincare, generating a list of 93 products. These products were then found at a local Target and Walgreens and online on Contact Allergen Management Program, SkinSAFE, and Consumer Product Information Database. Drugstore product labels were compared with online ingredient lists and analyzed for discrepancies. Results: There were 31 occurrences in which an allergen listed in the 2017 American Contact Dermatitis Society Core Allergen Series was omitted (present on the in-store label but missing from an online list.) Seven omissions occurred on Contact Allergen Management Program, 11 occurred on SkinSAFE, 5 occurred on Consumer Product Information Database, and 8 occurred on Amazon. Conclusions: Definitive treatment of allergic contact dermatitis is avoidance of allergens found on patch testing. These data suggest that patients may be at risk of inadvertent exposure to allergens from products, which are supposedly deemed safe according to online ingredient lists.